Da’wah, propagation of Islamic message through marshalling constructive bahaviours and positive attitudes - U Tun Aung, Maulana Akbar Shah (2017)
Being Muslims, many of us are willing to participate in Dawah activity at our respective community. However, we complain that it is not an easy job. One of the reasons is said to be lack of integrity and reliability in our dealing. Most of the times, our honesty is questioned for our reliability is hard to be acceptable. Sometimes, people are straightforward, then they are not successful for their approaches are not welcoming. People value humbleness, punctuality, gentleness, good communication, but the environment we live today does not encourage us to be balanced personality for they are most of the time teaching us deceit and lying. Then many of us surrender before the deceitful in most of the cases. Nevertheless, still the truth is that good attitude always wins the hearts of many. Therefore, we must make sure that we are serious about our good attitudes, particularly for those who involves in Da’wah. Allah SWT said: “O you who believe! Fear God, and be with those who are true (in word and deeds).” (Quran 9:119). Our prophet said: “Honesty descended from the Heavens and settled in the roots of the hearts of men (faithful believers), and then the Quran was revealed and the people read the Quran, (and learnt it from it) and also learnt from the sayings and traditions. Both the Quran and the traditions strengthened their honesty. (Saheeh Al-Bukhari). This paper emphasizes importance of positive attitudes essential for uplifting of righteousness with that a person is successful in all his assigned task particularly Daw’ah activity.